PENDAMPINGAN PENGELOLAAN DAN KEAMANAN WIFI GUNA MENDUKUNG OPERASIONAL UMKM BIMA FOTOKOPI - Sofi Ramadhani; Bunga Septiara Fitri; Jenny Pernanton; Abelto Abelto; Nini Nini; Rahmaita Rahmaita; Glegery Putri Hardoni (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2026)
For small business owners such as Bima Fotokopi, a Wi-Fi network is no longer merely an additional facility but has become an essential infrastructure supporting daily business operations. Internet connectivity is utilized to receive print documents through instant messaging applications, process digital payment transactions, and manage business administration. However, field observations revealed several weaknesses in the existing network management, including the use of easily guessed router passwords, the absence of bandwidth management, and the lack of a monitoring mechanism for connected devices. These shortcomings frequently resulted in unstable internet performance and increased the risk of unauthorized network access.To address these issues, a community assistance program was conducted to improve the knowledge and practical skills of the owner and employees of Bima Fotokopi in managing Wi-Fi network security. The implementation involved field observations, discussions to identify the partner's needs and existing challenges, and hands-on training in router configuration. The training materials covered the implementation of strong passwords, restriction of unauthorized device access, bandwidth management, and the establishment of periodic password update procedures.The results of the program demonstrated a significant improvement in the participants' understanding and ability to independently manage network security. The business owner and employees became capable of implementing basic network security configurations, restricting unauthorized access, and managing internet connectivity more effectively. These improvements contributed to enhanced network stability, stronger security, and more efficient business operations. Overall, the assistance program successfully strengthened the partner's capacity to manage its digital infrastructure independently, thereby reducing reliance on external technical support. ABSTRAKBagi pelaku usaha kecil seperti Bima Fotokopi, keberadaan jaringan Wi-Fi bukan lagi sekadar fasilitas tambahan, melainkan penggerak utama bisnis percetakan mereka. Setiap harinya, koneksi internet ini diandalkan tanpa henti untuk menerima dokumen cetak via aplikasi chat, memproses transaksi digital, hingga mengelola data administrasi internal toko. Namun, infrastruktur digital yang vital ini justru dibiarkan tanpa pengamanan yang memadai. Sandi router sangat mudah ditebak, kuota bandwidth jebol karena tidak dibatasi, dan pemilik tidak bisa memantau gawai asing yang ikut menumpang masuk. Akibat celah kelalaian ini, internet gerai mereka sering mendadak lambat dan sangat rawan disusupi pihak luar yang tidak bertanggung jawab. Berangkat dari masalah pelik tersebut, inisiatif pendampingan ini dirancang untuk membekali pemilik serta karyawan Bima Fotokopi dengan keterampilan praktis seputar proteksi jaringan. Proses edukasi dilakukan lewat pendekatan langsung, mulai dari pemantauan kondisi lapangan, diskusi santai mencari solusi terbaik, hingga praktik menyetel ulang konfigurasi perangkat router internet. Hasil dari kegiatan ini membawa perubahan signifikan bagi mitra. Sekarang, mereka sudah paham cara menyusun kata sandi yang rumit, membatasi akses pengguna asing, menjadwalkan ganti password berkala seminggu sekali, hingga mematikan sistem sementara saat koneksi mulai macet. Intervensi ini terbukti ampuh membuat operasional harian Bima Fotokopi menjadi jauh lebih aman, cepat, dan efisien. Lewat bekal ilmu berharga ini, mereka kini bisa mandiri mengelola keamanan digitalnya sendiri tanpa terus-menerus bergantung pada teknisi luar di masa depan.